EFFECTIVE MULTI-FACETED APPROACH TO SEVERE HYPERTRIGLYCERIDEMIA IN DIABETES AND HYPERTENSION: A CASE REPORT - Hassan, Hasliza Abu; Rahim, Siti Nadirah Ab; Rom, Fatimah Zahra Mohamad (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Diabetes mellitus, a metabolic disorder characterized by insulin deficiency, leads to increased release of free fatty acids and amino acids. This triggers glycogenolysis and gluconeogenesis, resulting in elevated production of very low-density lipoproteins (VLDL) and subsequent hypertriglyceridemia. Hypertriglyceridemia heightens the risk of atherosclerotic cardiovascular disease (ASCVD). CASE This case details the successful management of severe hypertriglyceridemia in a 45-year-old male with T2DM and hypertension. Despite non-compliance with treatment, the patient presented with asymptomatic severe hypertriglyceridemia, with a level of 45.4 mmol/L. A comprehensive approach involving pharmacological intervention, lifestyle modifications and laboratory consultation was implemented. After a thorough discussion on the impact of hypertriglyceridemia, the patient accepted the treatment regime. This included atorvastatin alongside existing anti-diabetic and anti-hypertensive medications, dietary counselling emphasizing a low-fat and high-fibre diet, regular exercise and treatment concordance. The patient demonstrated notable adherence to the prescribed regimen and incorporated smoking cessation and increased physical activity. Over three months, significant improvements were observed in serum triglyceride levels, glycaemic control and blood pressure, reflecting the efficacy of the management approach. Additionally, laboratory consultation aided in interpreting lipid profiles and identifying pseudohyponatremia secondary to analytical interference from lipemic samples. CONCLUSION This case highlights the efficacy of a holistic strategy in addressing hypertriglyceridemia in individuals with diabetes and hypertension. Integrating atorvastatin therapy, dietary adjustments and lifestyle modifications resulted in significant enhancements in triglyceride levels, glycaemic management and blood pressure, thereby reducing cardiovascular risks. Additionally, it highlights the crucial role of laboratory consultation in interpreting lipid profiles and identifying related anomalies in the test results, reinforcing the clinical significance of comprehensive patient care. The comprehensive strategy for addressing diabetic dyslipidaemia is delineated, incorporating medication, counselling, lifestyle modifications, and enhanced laboratory collaboration.